Molecular mapping of a stripe rust resistance gene in Chinese wheat cultivar Mianmai 41 - Yong REN; Sheng-rong LI; Yu-ming WEI; Qiang ZHOU; Xiao-ying DU; Yuan-jiang HE; You-liang ZHENG (Journal of Integrative Agriculture, 2015)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most damaging diseases of wheat. Chinese wheat cultivar Mianmai 41 showed high resistance against most of the prevailing Pst races in China. Genetic analysis of the F1, F2 and F2:3 populations from a cross between Mianmai 41 and a susceptible line Mingxian 169 indicated that resistance to Pst race CYR32 was conferred by a single dominant gene, temporarily designated as YrMY41. Molecular marker analysis placed the gene on chromosome 1B near the centromere. Six co-dominant genomic SSR markers Xwmc329, Xwmc406, Xgwm18, Xgwm131, Xgwm413, and Xbarc312, and one STS marker Xwe173 linked with the resistance gene. The two closest flanking SSR markers were Xgwm18 and Xwmc406, with genetic distances of 2.0 and 4.9 cM, respectively. A seedling test with 29 Pst isolates indicated the reaction patterns of Mianmai 41 were different from those of lines carrying Yr3, Yr9, Yr10, Yr15, Yr26, and YrCH42 on chromosome 1B. Allelic tests indicated that YrMY41 is likely a new allele at Yr26 locus.